2016
DOI: 10.1002/ijc.30366
|View full text |Cite
|
Sign up to set email alerts
|

Advanced colonic neoplasia in the first degree relatives of colon cancer patients: A colonoscopy‐based study

Abstract: We aimed to determine the risk of advanced neoplasms among a cohort of asymptomatic first degree relatives (FDRs) of patients with sporadic colorectal cancer (CRC) compared with matched controls. Data for patients with a diagnosis of CRC made between September 2013 and August 2014 were obtained from a population-based cancer registry system in Tehran. Screening colonoscopies were done for 342 FDRs and the findings were compared to those from 342 age- and gender-matched healthy controls without a family history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Population-based studies and randomized trials suggest that adherence to use of colonoscopy for screening in average and increased-risk populations is usually suboptimal . This undermines the efficacy of screening programs and underlines the need for alternative screening modalities that may limit the need for colonoscopy only to those participants with positive results. Several recently published guidelines support the use of FIT for screening of average-risk participants .…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies and randomized trials suggest that adherence to use of colonoscopy for screening in average and increased-risk populations is usually suboptimal . This undermines the efficacy of screening programs and underlines the need for alternative screening modalities that may limit the need for colonoscopy only to those participants with positive results. Several recently published guidelines support the use of FIT for screening of average-risk participants .…”
Section: Discussionmentioning
confidence: 99%
“…In our meta‐analysis, 13 out of 63 studies showed no significantly increased risk of CRC among individuals with family history of CRC [28, 39, 40, 42, 43, 56, 58, 59, 66, 72, 73, 79, 80], compared with other 50 studies that reported increased relative risk. Some possible explanations for this difference include the accuracy of self‐reported family history, varying quality of colonoscopy and experience of endoscopists across studies, the number of risk factors of CRC among subjects included in these studies, and differences in their region of residence.…”
Section: Discussionmentioning
confidence: 65%
“…The full texts of the remaining 812 articles were reviewed, with 45 articles fulfilling our eligibility criteria being selected, and 18 additional studies selected from reference lists of eligible articles. Therefore, a total of 63 articles were included in this meta‐analysis, including 9,284,074 patients (Supplementary Table 2 ) [242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586]. The earliest calendar year of subject enrollment was 1982.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, considering risk stratification to identify high-risk individuals was suggested to increase the effectiveness of CRC screening programs. Different risk factors, including age, gender, smoking, and family history, may be considered for the calculation of risk scores [229][230][231][232]. Combining the risk score with the FIT test was suggested as an effective strategy for more accurate detection of colorectal neoplasia in asymptomatic individuals [233][234][235].…”
Section: Combination and Risk-based Strategiesmentioning
confidence: 99%